Efek Analgesik Ekstrak Daun Kemangi (Ocimum sanctum L.) terhadap Tikus Putih (Rattus norvegicus) - Riza Setya Agrensa; Muchsin Doewes; . Samigun (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: Pain is a symptom of a disease that many felt by the people, the prevalence of pain in adults reach to 40% per day, while 89% felt the pain episode at least once a month. To overcome the pain that arises, people often use drugs is to reduce pain or analgesic. This research aims to find out whether there is an analgesic effect of kemangi extract (Ocimum sanctum L.) against the white mice (Rattus norvegicus). Methods: This research uses experimental methods to the post test only control group design. The research at the University of Setia Budi Surakarta performed. The subject of this research is 25 tail of a white mice (Rattus norvegicus), 3 months old with average weight 200 grams. First, subject adapted for 1 week, then not given to eat and drink for 18 hours before the treatment. The subject is divided into 5 groups. The negative control group was given aquades, while the positive control group was given aspirin. The third treatment group each got kemangi extract dosage of 225 mg/200 g body weight, 450 mg/200 g body weight, and 675 mg/200 g body weight. Pain induction method used is a medium hot plate, and then calculated the frequency jumps. The data obtained and analyzed by One-Way ANOVA and LSD. Results: The results of One-Way ANOVA test showed a significant difference between the five treatment groups. LSD test results showed a significant difference between the negative with the positive control group. Positive control group treated with the first and second doses showed a significant difference, but with the third dose treatment group showed no significant difference. This shows that only the third dose group has the analgesic effects. Conclusions: Of the three groups treated with kemangi extracts, only the third dose treatment groups shows analgesic effect on white mice. Keywords: kemangi extract, analgesic effects